DESCRIPTION OF MANASIK UMROH GUIDANCE TOWARDS INDEPENDENCE OF THE JAMAAH PT. MEIDA WISATA TOUR & TRAVEL MAKASSAR CITY - Uswatun Khasanah; Ruliaty, Ruliaty; Sherry Adelia Natsir Kalla (International Journal of Economic Research and Financial Accounting, 2024)
This study discusses the description of Umrah management guidance on the independence of PT. Meida Wisata Tour & Travel, which is motivated by the phenomenon of independence of Umrah pilgrims is the purpose of holding the Hajj. This study aims to describe the implementation of manasik guidance in realizing independent Umrah pilgrims at PT. Meida Tours Tour & Travel. Then the method used is descriptive qualitative. Data collection techniques in this study used interview, documentation, and observation methods. The source of data taken from the supervisor of Umrah manasik, and Umrah pilgrims PT. Meida Wisata Tour & Travel Makassar City. The results of this study show that first, the form and process of implementing the guidance of Umrah management of PT. Meida Wisata Tour & Travel Makassar City is good. Second, the implementation of manasik guidance in realizing the independence of PT. Meida Wisata is in accordance with the indicators of independence, where these indicators include: 1) understand the teachings and prohibitions prohibiting performing Hajj properly, 2) be able to maintain his health and safety, 3) meet his own needs during the process of performing Umrah until he returns to his homeland.